Techno-stress as a barrier in front of sustainable innovation: A research in food retail sector - Rüzgar, Nılüfer (My University, 2025)
In recent years, especially with Industry 4.0, which is in interaction with innovation, rapid digital developments in the world have affected not only the way organizations do business, but also employees. While the increase in the use of machinery and the fact that innovative artificial intelligence (AI) applications have become almost a part of daily life and increase the efficiency in organizations in a visible way, in some cases these developments cause negative effects on employees. One of these effects is the stress experienced by the employees when using technology in innovation based organizations. This stress experienced by employees is called “technostress”. The motivation of this paper is to research chain supermarket industry employees’ attitudes regarding technostress. In this context, a survey form, which includes demographic questions and the Technostress Scale with 14 items was prepared and delivered to the potential participants. 184 employees participated in the research. Descriptive statistics, factor analysis, non-parametric tests and post-hoc tests were applied to the gathered data. Findings show that there is statistically significant difference (p <0.05) between demographic characteristics (gender, marital status, age) of the participants and their attitudes towards technostress. In addition, according to the participants the most important items of the Technostress Scale are “I have co-workers who are more knowledgeable than me about the technology I use at my workplace”, “Frequent updates are made to the technological devices we use at my workplace” and “We constantly use new technologies at my workplace”. Furthermore, post-hoc tests show that, in the context of gender characteristics the difference stems from women participants, in the frame of marital status characteristics it is found that the difference stems from single participants. Finally, it is found that in the frame of age characteristics the difference stems from 30-39 age group. The fact that there is hardly no researches on technostress in the frame of chain supermarkets in literature, causes the current study to constitute originality. Therefore, it is expected that this research will shed light to both future researchers and professionals.
Keywords: Sustainability; Innovation; technology; technostress; sustainable innovation